Three New Records of Microleafhopper Genus Empoasca Walsh 1862 (Hemiptera: Cicadellidae: Typhlocybinae) From Bangladesh (Bangladesh Journal of Zoology, 2023)
The microleafhopper genus Empoasca Walsh, 1862 from Bangladesh is revised herein. With the existing species E. vitis (Göthe, 1875), another three species viz. E. kerri Singh-Pruthi, 1940, E. motti Singh-Pruthi, 1940 and E. onukii Matsuda, 1952 are described and reported first time from Bangladesh. Diagnostic descriptions, illustrations and a key to the Empoasca species from Bangladesh are provided.Bangladesh J. Zool. 51(1): 47-54, 2023